Lentigo Maligna of the head and neck: A retrospective study assessing surgical excision margins in a South African populationCapsule Summary - Johann de Wet, MBChB, MMed (Derm), MMed (Skin Cancer); Pieter J. du Plessis, MBChB, MMed (Derm); Johann W. Schneider, MBChB, MMed (Anat Path) (JAAD International, 2022)
Background: Lentigo maligna (LM) is a subtype of melanoma in situ that occurs on sun-damaged skin and is associated with significant subclinical extension beyond the clinical margins of the lesion. Objectives: This study aimed to determine if the standard recommended tumor excision margins for LM are adequate to achieve a 97% clearance rate and if any patient or tumor characteristics warranted wider margins. Methods: This study is a retrospective chart review of all patients who were diagnosed with LM of the head and neck and treated with staged excision. Results: The study included 64 patients. With a 6 mm surgical excision margin, only 60.9% of LM were completely excised. A 9 mm margin resulted in complete clearance of 71.9% of LM cases, and a 12 mm margin resulted in complete clearance in 90.6%. A surgical excision margin of 18 mm would have been required to excise 96.7% of tumors completely. Recurrent tumors (P = .01) and tumor size larger than 20 mm were associated with wider surgical excision margins (P = .154). Conclusion: This study of LM in a South African population corroborates that the standard surgical excision margins recommended by international melanoma guidelines for LM are inadequate to achieve a 97% clearance rate.